Teletrabalho: a tecnologia gerando uma nova forma de trabalho - Lenuzza, Leticia Maria Emanuelli (My University, 2014)
This study aims to discuss the telework before the Labour Rights and the huge transformations resulting from the technological process, as well as the factors that favour the dissemination of the labour both at distance and at home. Following this trajectory we explored the environmental modifications where organizations are looking for viable alternatives for their businesses, organizational structures and labour ways. Within this environment of mutations there exist professionals that perceive the relevance of innovations in the organizations, such as the telework. From this expectation arises the Telework Process, as a modern alternative of enterpreuneurial management, under the view of flexible labour alternatives, aiming to make the enterprises more competitive and dynamic, different from those that are still dangerously used to stability and to the routine of the traditional work. In order to reach our goal we followed the directions already opened by the doctrine, adding a systemic sociologic focus, opened, that allows us to rethink the labour world and the challenges of the post-industrial society. This brings about the need of a new sociology to observe the transformations in labour relations concomitantly to a new technological and productive paradigm.
O presente estudo tem como objetivo discutir o teletrabalho perante o Direito do Trabalho e as grandes transformações advindas do processo tecnológico. Os fatores que favorecem a disseminação do trabalho a distância e a domicílio. Nesta trajetória, exploramos as alterações ambientais onde as organizações estão buscando alternativas viáveis para seus negócios, estruturas organizacionais e formas de trabalho. Dentro desse ambiente de mutações, existem profissionais que percebem a relevância das inovações nas organizações, como é o caso do teletrabalho. A partir dessa expectativa, surge o Processo de Teletrabalho, como uma alternativa moderna de gestão empresarial, sob o enfoque das alternativas de trabalho flexível para tornar as empresas mais competitivas e dinâmicas, diferentes daquelas outras que ainda estão perigosamente acostumadas à estabilidade e à rotina do trabalho tradicional. Para tanto, percorremos as direções já abertas pela doutrina, juntando um enfoque sociológico sistêmico, aberto, que nos permite repensar o mundo do trabalho e os desafios na sociedade pós-industrial. Com isso, faz-se necessária uma nova sociologia para observar as transformações nas relações de trabalho concomitantes ao novo paradigma produtivo e tecnológico.
Keywords: Direito do trabalho; Mundo do trabalho; Teletrabalho; Flexibilização; Tecnologia; Trabalho; Labor world; Telework; Labor laws and legislation; Flexibilization; Technology